Highly efficient heritable plant genome engineering using Cas9 orthologues from Streptococcus thermophilus and Staphylococcus aureus. (December 2015) - Steinert, Jeannette; Schiml, Simon; Fauser, Friedrich; Puchta, Holger
Summary: The application of the clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system of Streptococcus pyogenes (SpCas9) is currently revolutionizing genome engineering in plants. However, synthetic plant biology will require more complex manipulations of genomes and transcriptomes. The simultaneous addressing of different specific genomic sites with independent enzyme activities within the same cell is a key to this issue. Such approaches can be achieved by the adaptation of additional bacterial orthologues of the CRISPR/Cas system for use in plant cells. Here, we show that codon‐optimised Cas9 orthologues from Streptococcus thermophilus (St1Cas9) and Staphylococcus aureus (SaCas9) can both be used to induce error‐prone non‐homologous end‐joining‐mediated targeted mutagenesis in the model plant Arabidopsis thaliana at frequencies at least comparable to those that have previously been reported for the S. pyogenes CRISPR/Cas system. Stable inheritance of the induced targeted mutations of the ADH1 gene was demonstrated for both St1Cas9‐ and SaCas9‐based systems at high frequencies. We were also able to demonstrate that the SaCas9 and SpCas9 proteins enhance homologous recombination via the induction of double‐strand breaks only in the presence of their species‐specific single guide (sg) RNAs. These proteins are not prone to inter‐species interference with heterologous sgRNA expression constructs. Thus, the CRISPR/Cas systems of S. pyogenes and S. aureus should be appropriate for simultaneously addressing different sequence motifs with different enzyme activities in the same plant cell. Significance Statement: The CRISPR/Cas system is now the major tool for genome engineering, but so far only Cas9 from Streptococcus pyogenes has been used in plants. Here we demonstrate that Cas9 orthologues, with different sequence motifs and different enzyme activities, can be used simultaneously in the same cell.